Appraisal of translocation pathways for displaying ankyrin repeat protein on phage particles - Nangola S. (2017)
Depending on the molecular properties of the proteins of interest (POI), the rate of success in displaying proteins on phage particles is unpredictable. Formation of polypeptide tertiary structure in the cytoplasm occasionally results in low level display on viral particles. Here we assessed the influence of different leader peptides on the display of a premature cytoplasmic folding protein, ankyrin repeat protein (ARP), via the minor coat protein pIII. These peptides include the Sec, SRP and Tat pathways. The results demonstrated that the Sec and SRP pathways were capable of displaying the protein on the viral particle, whereas the Tat pathway failed to do so. Interestingly, the Tat pathway efficiently directed ARP through its translocon without fusing with pIII. Furthermore, the soluble form of ARP was detected in Escherichia coli periplasm.© 2010 Elsevier Inc. All rights reserved.